JA:2021-31. Does the Use of a Nasal Lavage Intervention Improve Pulmonary Function for Dairy Workers?. Issue 3 (2nd July 2020) - Seidel, James; Erlandson, Grant; Labadie, Julia D.; Magzamen, Sheryl; Sharp, Julia; Jones, Ken; Nonnenmann, Matthew; Reynolds, Stephen J.; Schaeffer, Joshua W.
ABSTRACT: Purpose : Dairy workers are at the frontline of exposure to bioaerosols, which typically contain bacteria and associated pro-inflammatory constituents (e.g., endotoxin). As such, dairy workers are at an increased risk for respiratory illness, most likely mediated through a strong proinflammatory response. Very few studies have systematically evaluated control strategies to reduce exposure and improve health. Given the challenges and limitations of implementing engineering controls, we propose the use of a low-cost and low-burden intervention. Hypertonic saline (HTS) was recently shown to attenuate inflammation in trauma patients. Here, we conducted an intervention to administer HTS in a nasal lavage to determine if the inflammatory response was mitigated and if the airway function improved among dairy workers. Methods : Ten participants were recruited from a large herd dairy and randomly assigned to treatment (n = 5) and control groups (n = 5). Each participant received normotonic saline (308 mOsm) nasal lavage (NL) before their shift over 5 consecutive days. After each shift, the treatment group received HTS, while the control group received normotonic saline. All samples were analyzed for 10 different cytokines using a multiplex assay. Spirometry was performed pre- and post-shift to examine forced expiratory volume in one second, forced vital capacity and the subsequent ratio, and peak expiratory flow rate (PEFR). Personal breathing zone samples for inhalable bioaerosols were collected across the work shift; mass concentrations and endotoxin abundance were determined by gravimetry and a fluorescent assay, respectively. Statistical analyses and models were performed using SAS. Results/Findings : Differences in pro-inflammatory cytokines were observed. There was an interaction effect on IL-10 between treatment, day, and time of day, indicating promotion of anti-inflammatory effect. The treatment group experienced an increase in PEFR change (0.76 L, p = 0.12) near statistical significance; no statistically significant differences were observed in the other spirometry measures. Both groups of dairy workers in this study experienced less of a decline in cross-shift pulmonary function when compared to other studies. Practical Application : The HTS nasal lavage is designed as a low-cost intervention that can be self-administered before and after every shift across other agricultural operations. This study was limited by small sample size and warrants further investigation.